Analysis of the economic efficiency criteria and equity while determining the taxes - Natalia A. Prodanova, Nataliya S. Plaskova,; Leontyev, Alexey N.; Pavel S. Probin, Irina P. Ratnikova, Kirill S. Ratnikov, (Opción, 2019)
The aim of the study is to investigate the criteria of economic efficiency and equity while determining the optimal amount of taxes comparative qualitative research methods. The authors show that while determining the rational level of the tax burden, it is necessary to determine and describe in terms of quantity the totality of factor connections and parameters of equity and efficiency, taking into account the specific conditions of taxation of the specific country. In conclusion, using the offered approach with the application of alternative optimization method, allowing to establish a taxation scheme accepted by the majority of the population